Faktor-faktor yang Mempengaruhi Kinerja Pegawai - Suwarto Suwarto (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
The goal in this study to determine a general overview of the work ability, work dicipline and employeesperformance, in addition to knowing about the effect of work ability and work dicipline partially and simultaneously on employee performance. Research using explanatory research with a quantitative approach and data collection through a questionnaire. The sample used by 35 employees remain at the Badan Kepegawian dan Pengembangan Sumber Daya Manusia Kabupaten Muaro Jambi. Analysis of the data used is descriptive analysis method and inferential analysis by observing the classical assumption test and multiple linear analysis. The results show that the employability and dicipline affect the performance of employees is 82,3%. While the remaining 17,7% variable employee performance will be affected by any variables as: wages, job security, working conditions, achievements, training, work experience and others.